Performance Analysis of a Hybrid One-Sided Magnetic Exciter Mounted on a Piezoelectric Stack - A. Nandi; S. Neogy (Shock and Vibration)
The present work proposes a non-contact hybrid exciter especially useful for harmonic excitation of lightly damped structures/rotors. In the proposed exciter an electromagnet is placed on a piezoelectric stack and the extension of the piezoelectric stack is made almost equal to the displacement of the structure using a simple tracking control. This largely eliminates stiffness coupling between the structure/rotor and the exciter and non-linearity in the excitation force due to the vibration of the structure/rotor. The stiffness and inertia of the piezoelectric stack is considered in the analysis. A SIMULINK model of the combined structure and the exciter is developed for a full time-domain simulation of the excitation system.